Knowledge and utilization of intermittent preventive treatment for malaria among pregnant women attending antenatal clinics in primary health care centers in rural southwest, Nigeria: a cross-sectional study - Ajayi Ikeoluwapo O; Falade Catherine O; Akinleye Stella O (BMC, 2009)
Abstract Background Intermittent preventive treatment for prevention of malaria in pregnancy (IPTp) is a key component of malaria control strategy in Nigeria and sulfadoxine-pyrimethamine (SP) is the drug of choice. Despite the evidence of the effectiveness of IPTp strategy using SP in reducing the adverse effects of malaria during pregnancy the uptake and coverage in Nigeria is low. This study set out to assess the use of IPTp among pregnant women attending primary health centres in the rural area and determine factors that influence the uptake. Methods A cross-sectional study was carried out between July and August 2007 among 209 pregnant women selected by systematic random sampling from antenatal care attendees at primary health care in a rural Local Government Area of Ekiti State, Nigeria. Information on knowledge of IPT, delivery, adherence and acceptability was obtained using an interviewer administered questionnaire. Descriptive statistics such as means, range, proportions were used. Chi-square test was used to examine association between categorical variables. All analyses were performed at 5% level of significance. Results One hundred and nine of 209 (52.2%) respondents have heard about IPTp but only 26 (23.9%) were able to define it. Fifty seven (27.3%) reported to have received at least one dose of IPTp during the index pregnancy and all were among those who have heard of IPTp (52.3%). Twenty one of the 57 (36.8%) took the SP in the clinic. Only three of the twenty-one (14.3%) were supervised by a health worker. Twenty two of the 36 women (61.1%) who did not take their drugs in the clinic would have liked to do so if allowed to bring their own drinking cups. Almost half (43.9%) of those who had used IPTp during the index pregnancy expressed concern about possible adverse effect of SP on their pregnancies. Periodic shortages of SP in the clinics were also reported. Conclusion In this study, IPTp use among pregnant women was very low and there was poor adherence to the Directly Observed Therapy (DOT) scheme. Concerted effort should be made to increase awareness of IPTp among the public especially women of child bearing age. Health workers should also be trained and monitored to ensure adherence.